2016
DOI: 10.1037/ccp0000061
|View full text |Cite
|
Sign up to set email alerts
|

Partner accommodation moderates treatment outcomes for couple therapy for posttraumatic stress disorder.

Abstract: Objective Partner accommodation of posttraumatic stress disorder (PTSD) symptoms (i.e., altering one’s own behaviors to minimize patient distress and/or relationship conflict due to patients’ PTSD symptoms) has been shown to be positively associated with patient and partner psychopathology and negatively associated with patient and partner relationship satisfaction cross-sectionally. However, the prognostic value of partner accommodation in treatment outcomes is unknown. The goals of the present study were to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
52
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 22 publications
5
52
2
Order By: Relevance
“…However, partner accommodation is linked with greater distress in both trauma survivors and partners (e.g., Fredman et al, 2014; Fredman et al, 2016), which also predicts worse outcomes for those with PTSD (e.g., Evans et al, 2009). Thus, individual and conjoint treatments for PTSD should clearly lay out a treatment rationale for both members of the couple and provide partners with psychoeducation about PTSD symptoms to stem potentially distressing, burdensome, or unhelpful accommodating behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, partner accommodation is linked with greater distress in both trauma survivors and partners (e.g., Fredman et al, 2014; Fredman et al, 2016), which also predicts worse outcomes for those with PTSD (e.g., Evans et al, 2009). Thus, individual and conjoint treatments for PTSD should clearly lay out a treatment rationale for both members of the couple and provide partners with psychoeducation about PTSD symptoms to stem potentially distressing, burdensome, or unhelpful accommodating behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Fredman, Vorstenbosch, Wagner, Macdonald, and Monson (2014) found that scores on a newly created measure of partner accommodation of PTSD were strongly associated with partners’ perceptions of trauma survivors’ PTSD symptom severity and with additional distress in romantic partners. Moreover, greater accommodation interfered with natural symptom remission in a sample of largely female, civilian trauma survivors (Fredman et al, 2016). However, prior work did not test the direction of effects over time, but rather looked at cross-sectional associations of PTSD and accommodation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, partners may engage in accommodating or other treatment-interfering behavior that contributes to the dyad's relationship distress and create impediments to recovery from PTSD (Fredman, Vorstenbosch, Wagner, Macdonald, & Monson, 2014), but including partners in CBCT for PTSD helps to blunt the impact of these maladaptive partner behaviors (Fredman, Pukay-Martin, Macdonald, Wagner, Vorstenbosch, & Monson, 2015). Additionally, maladaptive relationship-based behaviors, such as poor communication, may interfere with adaptive trauma disclosure, and poor conflict management may work to maintain the symptoms of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to aid communication skills and making more accurate attributions about symptoms (e.g., lack of engagement in family outings due to PTSD-related avoidance rather than disinterest in the family) might promote positive treatment outcome and prevent inadvertent interference with treatment (Fredman et al, 2016). Engaging partners in some aspects of individual treatment may be helpful among individuals who are unwilling or unable to engage effectively in dyadic interventions (Monson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%